Orthodontists' and laypeople's perception of smile height aesthetics in relation to varying degrees of transverse cant of anterior teeth - Shiyan Huang; Xu Qian; Shuhao Xu; Nanquan Rao; Xiaobing Li (Sciendo, 2016)
To determine the effect of varying the transverse cant of the anterior teeth on orthodontists' and laypeople's perceptions of smile aesthetics, and the influence that smile height has on this perception.